The Capacitor Handbook
XII, 126 p. 5 illus.
Keywords: A long and varied experience in many areas of electronic circuit design has convinced me that capacitors are the most misunderstood and misused electronic component. This book provides practical guidance in the understanding, construction, use, and application of capacitors. Theory, combined with circuit application advice, will help to under stand what goes on in each component and in the final design. All chapters are arranged with the theory of the dielectric type discussed first, followed by circuit application information. With all chapters arranged in the same manner, this will make reading and using this book for reference easier. A practical glossary of terms used in the capacitor industry is included. The first chapter covers basic information that applies to all types of capacitors. Each following chapter addresses a different capacitor dielectric. This book could have been titled: 'Everything You Wanted To Know About Capacitors, But Were Afraid To Ask .. .' ix Preface THE CAPACITOR HANDBOOK Chapter 1 Fundamentals For All Capacitors For all practical purposes, consider only the parallel plate capacitor as illustrated in Fig. 1.1-two conductors or electrodes separated by a dielectric material of uniform thickness. The conductors can be any material that will conduct electricity easily. The dielectric must be a poor conductor-an insulator. Conductor (Electrode) Dielectric ,; ~; ...--~ Conductor (Electrode) 1..-----Wire to Outside World Fig. 1.1 The Parallel-Plate Capacitor Fig. 1.2 illustrates the symbol for a capacitor used in schematic diagrams of electronic circuits. The symbol resembles a parallel-plate model.